Profiling of Modified Chitosan-Based Composites as Tetracycline Hydrochloride Drug Release Systems - Anjartikasari, Nurul; Yuanita, Emmy; Dharmayani, Ni Komang Tri; Sudirman, Sudirman; Sudewianingsih, Ni Made; Ulfa, Maria (Hasanuddin University, 2024)
Controlled drug release systems (DRS) are a crucial technology in the medical field, and they continue to be developed today. Chitosan is useful in manufacturing-controlled drug release systems due to its non-toxic, biodegradable, and biocompatible properties. However, it has some limitations when it comes to its physical and mechanical properties. Combining chitosan with other materials, such as bacterial cellulose (BC), graphite (Gr), ZnO, and TiO2, can improve its mechanical properties and antibacterial activity. This study aims to synthesize Chi/BC/Gr/TiO2 and Chi/BC/Gr/ZnO composites as drug release systems. When tested with TCH, an antibiotic model, the drug release kinetics of the composite followed the Hixson-Crowell and Korsmeyer-Peppas kinetics models. Additional tests for physical and mechanical properties, as well as antibacterial activity, have also been conducted. Mechanical properties in terms of tensile strength and Young’s modulus in composites with adding Gr, TiO2, and ZnO have higher values than Chi/BC alone. Compared to positive control, both TCH-loaded composites show higher inhibition against S. aureus bacteria. Based on the results of this study, composite Chi/BC/Gr/TiO2 and Chi/BC/Gr/ZnO have potential applications as DRS such as wound dressing.